Applications of nanomedicine-integrated phototherapeutic agents in cancer theranostics: A comprehensive review of the current state of research - Shoaib Ambreen; Javed Shamama; Tabish Mohammad; Khan Mohammad Ehtisham; Zaki Mehvash; Alqahtani Saad S.; Sultan Muhammad H.; Ahsan Waquar; Afzal Mohd (Nanotechnology Reviews, 2024)
Innovative approaches such as photodynamic therapy (PDT) and photothermal therapy (PTT) have made nanomedicines a promising frontier in cancer theranostics. The combination of nanocarriers with photothermal agents and photosensitizers (PSs) has shown excellent promise for the diagnosis and the treatment of cancer, primarily at the cellular, vascular, and tumor microenvironment level. Using nanocarriers in PDT has revolutionized precision and efficacy, allowing the drug to reach cancer cells faster and offering high enhancing PS accumulation. These agents are activated by light of specific wavelengths, leading to localized cytotoxicity, offering highly selective cancer therapy. Nanomaterials such as gold and silver nanoparticles have enabled remarkable progress in cancer hyperthermia using PTT. The unique optical properties of these nanoparticle-based nanomedicines make them ideal candidates for converting light energy into heat, selectively ablating the cancer cells. In this review, nanomedicine-integrated phototherapeutic agents are discussed and the most important recent developments in PDT and PTT are examined, as well as how nanoparticle-based formulations improve diagnosis and treatment. In addition, nanocarriers used in cancer phototherapy and their mode of action are discussed. Nanocarriers are useful for drug delivery as well as for imaging and diagnostic purposes during cancer treatment. In this review, we explore the role of nanoparticles in improving phototherapy precision and selectivity while minimizing collateral tissue damage. It specifies a comprehensive impression of the current research on cancer therapy, underscoring its potential to revolutionize the treatment paradigm by highlighting the current state of research.